An Exploration of Elementary School Students' Experiences in Using Educational Game Apps to Increase Empathy - Pulungan, Nurfazri; Bunyamin, Bunyamin; Sumartiningsih, Sri; Yuwono, Agus (Universitas Pahlawan Tuanku Tambusai, 2025)
Instilling empathy values from an early age is an important aspect in children's social-emotional development, especially at the elementary school level. Along with the advancement of digital technology, educational game applications are beginning to be used as learning media that are not only informative, but also emotionally transformative. This study aims to explore how the experience of elementary school students in using educational game applications can contribute to increased empathy. The method used is a qualitative approach through literature review of various relevant previous studies. The results of the study showed that educational games designed with strong narratives, role-play features, and social interaction in the game, were able to build emotional attachment of players to the characters, as well as facilitate perspective taking. This study concludes that interactive and meaningful educational games are effective in increasing the empathy of elementary school students by building emotional connectedness and social sensitivity, so that it becomes an important learning medium in character formation from an early age.